Ocular manifestation and visual outcomes in herpes zoster ophthalmicus: a prospective study from a tertiary hospital of Eastern India - Mayukh Goswami (Press of International Journal of Ophthalmology (IJO PRESS), 2021)
AIM: To estimate the magnitude of different ocular manifestation in clinically established herpes zoster ophthalmicus (HZO) patients and assessment of the visual outcome after two months of initial examination. METHODS: An observational prospective study was conducted on 42 clinically diagnosed Tzanck smear positive cases HZO to observe the occurrence and frequency of different ocular manifestation and their visual outcome in 10-month period with 2mo follow up. Full ophthalmological examination using slit lamp, non-contact tonometry, applanation tonometry, direct and indirect ophthalmoscope were performed. RESULTS: Out of 42 patients of HZO, 33 had one or more type of ocular manifestation staring from lid skin involvement to conjunctivitis, keratitis, uveitis, increased intraocular pressure (IOP) and optic neuritis but no retinal manifestation. More number of HZO cases and ocular manifestation were found with advancement of ages. Young HZO patients were more associated with human immunodeficiency virus (HIV) infection and HIV infected people with HZO infection had more ocular manifestation. Male to female ratio was 2:1 among HZO cases but ocular manifestation occurred more among males. Female with advanced age were involved more. Lid involvement (73.81%), conjunctivitis (69.05%), and keratitis (59.52%) were most common ocular manifestation followed by anterior uveitis (30.95%) and episcleritis (11.90%). Ocular hypertension (42.86%) was associated with almost every ocular manifestation. Among the cases of more than 45 years of age, 9.52% patients acquired 6/6 vision compared to 7.14% patients at and below 45 years of age after 8wk of follow up. CONCLUSION: The visual outcomes are poor in HZO with advanced age group. Visual outcome of the affected eyes is poor than unaffected eyes. The loss of vision is mainly due to keratitis, anterior uveitis, posterior uveitis, and optic neuritis.